STRUKTUR KOMUNITAS AMPHIBI DI TAMAN WISATA ALAM (TWA)KERANDANGAN DALAM UPAYA PENYUSUNAN MODUL EKOLOGI HEWAN - Sarwenda Sarwenda; Subagio Subagio; Ali Imran (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: The aims of this research is to analyze the structure of amphibian communities in natural park Kerandangan, and to describe the validity of animal ecology module that developed. The population of this research is all amphibians in natural park Kerandangan. The sample used in this research is the number of individuals amphibians (ordo anura) captured at the time of investigation. The method used is visual encounter survey (VES), and combined with capture sign release and recapture (CSRR). Data collection techniques used in this research were (1) basic data, (2) validation. Total 1 species of amphibians have been identified, that is families Bufonidae as many as 15 individuals. This research different from Kadir (2011) with ± 5 year periode in natural park Kerandangan have been declaine in community structure. The result of this research obtained from the calculation of data analysis as follows: (1) the diversity index (H = 0,186), (2) Simpson dominance index (C) = 0,0044, (3) the relative abundance is 6,7%, (4) density on 1 individual/100 m, (5), evenness index = 0,0686, (6) validation sheet with the calculation result of test readability by 20 four semesters graduate student, obtained average value = 3,66 with 73,1% level of achievement, the average from the material expert = 4,3 with 86% level of achievement, the average result from the appereance expert = 4,1, with 82% level of achievement, as well as the average value from the linguistics expert = 4, with 80% level of achievement, from the calculation based on expert judgment, can be declared that the module of animal ecology suitable for use a module.